Phylogeography of two cryptic species of African desert jerboas (Dipodidae: Jaculus) - (:unkn) unknown (My University, 2012)
The lesser Egyptian jerboa Jaculus jaculus is a desert dwelling rodent that inhabits a broad Arabian–Saharan arid zone. Recently, two distant sympatric lineages were described in North-West Africa, based on morphometric and molecular data, which may correspond to two cryptic species. In the current study, phylogenetic relationships and phylogeographical structure among those lineages and geographical populations from North Africa and the Middle East were investigated. The phylogeographical patterns and genetic diversity of the cytochrome b gene (1110 bp) were addressed on 111 jerboas from 41 localities. We found that the variation in Africa is partitioned into two divergent mitochondrial clades (10.5% divergence relating to 1.65–4.92 Mya) that corresponds to the two cryptic species: J. jaculus and J. deserti. Diversifications within those cryptic species/clades were dated to 0.23–1.13 Mya, suggesting that the Middle Pleistocene climatic change and its environmental consequences affected the evolutionary history of African jerboas. The third distant clade detected, found in the Middle East region, most likely represents a distinct evolutionary unit, independent of the two African lineages
Keywords: African Research